Tumor in the plantar region: dermatofibrosarcoma protuberans in an infrequent topography, - Perazzoli,Simone (2020)
Abstract Dermatofibrosarcoma protuberans is a rare mesenchymal tumor; it is locally aggressive and presents high rates of local recurrence. It may present as a nodular or plaque vegetating lesion. It mainly affects the trunk and proximal limbs, being rare in the distal extremities. Biopsy and immunohistochemistry help confirm the diagnosis. The authors report a case of dermatofibrosarcoma protuberans with plantar region involvement, a rare presentation. To the best of the authors’ knowledge, only 11 cases of involvement of the feet were described in the international literature.